2021
DOI: 10.3390/plants10102227
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Options to Control Naturalised Infestations of Cereus uruguayanus in Rangeland Environments of Australia

Abstract: While there are many high profile Opuntioid cactus species invading rangeland environments in Australia, Cereus uruguayanus Ritt. ex Kiesl. has also naturalised and formed large and dense infestations at several locations. With no herbicides registered for control of C. uruguayanus in Australia, the primary aim of this study was to identify effective herbicides to control it using a range of techniques. This involved a large screening trial of twelve herbicides and four techniques, followed by a rate refinemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The results of the foliar herbicide study support previous work demonstrating that mixtures with triclopyr and picloram or with triclopyr, picloram, and aminopyralid, are highly effective as foliar applications against other woody species (Campbell et al 2021; Gawn et al 2013; Webb and Harrington 2005). However, the evidence in this study was not strong that the mixture was much more effective against old man's beard than triclopyr alone, or metsulfuron, which are less persistent in the environment.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The results of the foliar herbicide study support previous work demonstrating that mixtures with triclopyr and picloram or with triclopyr, picloram, and aminopyralid, are highly effective as foliar applications against other woody species (Campbell et al 2021; Gawn et al 2013; Webb and Harrington 2005). However, the evidence in this study was not strong that the mixture was much more effective against old man's beard than triclopyr alone, or metsulfuron, which are less persistent in the environment.…”
Section: Resultssupporting
confidence: 84%
“…Aminopyralid structurally resembles picloram and is likewise persistent in plant tissue and soil, with high soil mobility (Ferrell et al 2006; Kline et al 2005; MacBean 2010). These pyridine herbicides are commonly mixed together to achieve improved control of brush weeds (Campbell et al 2021; Gawn et al 2013; Moore et al 2010; Tran et al 2015; Webb and Harrington 2005). Although metsulfuron can be highly mobile in some soils (Thompson et al 1992; USDA-ARS 1995), studies have shown it to have relatively low residual soil activity, from 5 to 63 d after treatment (Harrington et al 2017; Ismail and Lee 1995; Trabue et al 2006; Tran et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven cactus species are listed as Weeds of National Significance in Australia, all of which belong to the Opuntioideae subfamily (flattened-padded growth forms) and the genera Opuntia and Cylindropuntia (Sheehan and Potter 2017). However, several species from other subfamilies are emerging or major weeds in Australia (Campbell et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cereus uruguayanus is also present in several locations in New South Wales (Hosking et al 2007). It is most prevalent in mixed eucalypt–brigalow woodlands on light clay soils but also occurs in areas of cleared improved pasture and on a range of soil types (Campbell et al 2021). In South Africa, the mealybug, Hypogeococcus sp.…”
Section: Introductionmentioning
confidence: 99%